2015
DOI: 10.3324/haematol.2014.121590
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-1 signaling via CD63 triggers granulopoiesis and neutrophilia in mice

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nrent study, we investigated whether TIMP-1 affects neutrophil homeostasis. We show that TIMP-1 signaling via CD63 triggered granulopoiesis in the bone marrow (BM) resulting in increased systemic neutrophil blood counts. Our findings reveal a new function of TIMP-1 on immune cell homeostasis, and may provide a link to the frequently described correlation of high TIMP-1 levels with inflammatory diseases in the clinic. Methods Animal experimentsAnimal experiments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 53 publications
(77 reference statements)
4
36
0
1
Order By: Relevance
“…Even though TIMP‐1 has shown good antiapoptotic activity in other cancers, there are some research evaluating the function of TIMP‐1 in breast cancer cell growth and there is no consensus in these studies . It was reported that TIMP‐1 inhibits cell growth in MCF‐10A normal breast epithelial cells by decreasing cyclin D1 levels . Thus, although there are several distinct signaling pathways and hypothetical receptors in TIMP‐1 function, the mechanisms underlying the role of TIMP‐1 in breast cancer stay uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though TIMP‐1 has shown good antiapoptotic activity in other cancers, there are some research evaluating the function of TIMP‐1 in breast cancer cell growth and there is no consensus in these studies . It was reported that TIMP‐1 inhibits cell growth in MCF‐10A normal breast epithelial cells by decreasing cyclin D1 levels . Thus, although there are several distinct signaling pathways and hypothetical receptors in TIMP‐1 function, the mechanisms underlying the role of TIMP‐1 in breast cancer stay uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that TIMP‐1 inhibits cell growth in MCF‐10A normal breast epithelial cells by decreasing cyclin D1 levels . Thus, although there are several distinct signaling pathways and hypothetical receptors in TIMP‐1 function, the mechanisms underlying the role of TIMP‐1 in breast cancer stay uncertain. In our study, the tissue TIMP‐1 levels were increased in whole therapeutic groups, we think that TIMP‐1 levels may elevate due to decrease MMP‐9 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the leukocyte cytokine and chemokine profile in both the HAR and NHAR groups showed a trend toward a higher anti-inflammatory transfusion bias with a significant increase post-transfusion compared with pretransfusion in MMP-9 and, to a lesser extent, in IL-10. Tissue metalloproteinase inhibitor protein-1 (TIMP-1) is a protein that inhibits MMP-9 activity 19 and also interacts with CD63, 20 which may account for our observation that MMP-9 increased in plasma, whereas CD63 decreased in all leukocytes post-transfusion. Decreased CD63 expression may result from intracellular binding to TIMP-1, resulting in higher levels of extracellular MMP-9.…”
Section: Discussionmentioning
confidence: 88%
“…Timp1 -/mice have reduced BM HSC and HSPC numbers relative to WT (Table 2), and their decreased long-term repopulation potential has been shown to arise from reduced quiescence [103]. Systemic TIMP1 elevation in mice by infection with a transgenic adenovirus augmented the proliferation of BM progenitors and enhanced their differentiation towards granulopoiesis [104]. The use of nonprotease-inhibiting TIMP1 and of CD63 -/mice in some experiments suggests that this was due to growth factor activity of TIMP1 binding to CD63 rather than to metalloprotease inhibition.…”
Section: Timps In Hematopoiesismentioning
confidence: 99%